2016
DOI: 10.1371/journal.pone.0151766
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes of Intraocular Pressure in Elderly People in Southern China: Lingtou Eye Cohort Study

Abstract: PurposeTo study age-related changes of intraocular pressure (IOP) and assess the cohort effect in both cross-sectional and longitudinal settings among elderly Chinese adults.MethodsParticipants were enrolled from the Lingtou Eye Cohort Study with Chinese government officials aged 40 years and older at baseline and received physical check-up and ocular examinations from 2010 to 2012. IOP was measured using a non-contact tonometer according to standardized protocols, as well as systolic blood pressure (SBP), dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 30 publications
10
26
0
Order By: Relevance
“…Mean IOP reported in our study (15.3 AE 3.0 mmHg at baseline) was similar to that reported in other studies based on Chinese populations (15.6 AE 3.0 mmHg in Beijing and 15.3 AE 2.3 mmHg in Guangzhou, using a noncontact pneumotonometer), 18,25 and higher that reported in Japan (11.9 AE 2.5 mmHg, using a noncontact tonometer) and Korea (13.6 AE 2.5 mmHg, using automated non-contact tonometers). 11,13 This discrepancy on IOP distribution may be attributable to ethnicity and different methods of tonometry are used.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Mean IOP reported in our study (15.3 AE 3.0 mmHg at baseline) was similar to that reported in other studies based on Chinese populations (15.6 AE 3.0 mmHg in Beijing and 15.3 AE 2.3 mmHg in Guangzhou, using a noncontact pneumotonometer), 18,25 and higher that reported in Japan (11.9 AE 2.5 mmHg, using a noncontact tonometer) and Korea (13.6 AE 2.5 mmHg, using automated non-contact tonometers). 11,13 This discrepancy on IOP distribution may be attributable to ethnicity and different methods of tonometry are used.…”
Section: Discussionsupporting
confidence: 90%
“…31 Multiple previous studies, either cross-sectional or longitudinal in design, had reported that a higher BMI was associated with a higher risk of glaucoma. 33 Based on our findings and other related longitudinal studies in China, 18,22,25 we suggest that higher BMI could lead to an increase in IOP in Chinese population, and this could be part of reason that younger generations had higher IOP compared to the elderly in cross-sectional analysis. 16 However, data from the Nurses' Health Study and the Health Professionals Follow-up Study showed that women with a higher BMI had a lower risk of primary open angle glaucoma.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Following age-based stratification, the Beijing Eye Study reported an IOP decline over time but only after 75 years of age 42. In the Lingtou Eye Cohort Study,43 a cross-sectional analysis revealed age-associated IOP reduction that was negated by a longitudinal analysis uncovering a possible cohort effect. The effect of age on IOP depends on one’s ethnicity and associated ocular or systemic conditions.…”
Section: Discussionmentioning
confidence: 99%